Adjustable Velcro® Compression Devices are More Effective than Inelastic Bandages in Reducing Venous Edema in the Initial Treatment Phase: A Randomized Controlled Trial. Issue 3 (September 2015) - Mosti, G.; Cavezzi, A.; Partsch, H.; Urso, S.; Campana, F.
Abstract : Objective/Background: The objective of this study was to compare the efficacy and comfort of inelastic bandages (IBs) and adjustable Velcro ® compression devices (AVCDs) in reducing venous leg edema in the initial treatment phase. Methods: Forty legs from 36 patients with untreated venous edema (C3EpsAsdPr) were randomized to two groups. Patients in the first group received IBs ( n  = 20) and those in the second AVCDs ( n  = 20). Both compression devices were left on the leg day and night, and were renewed after 1 day. Patients in the AVCD group were asked to re-adjust the device as needed when it felt loose. Leg volume was calculated using the truncated cone formula at baseline (T0), after 1 day (T1) and after 7 days (T7). The interface pressure of the two compression devices was measured by an air filled probe, and the static stiffness index calculated after applying compression at T0 and T1, and just before removal of compression on T1 and T7. Patient comfort with regard to the two compression systems was assessed by grading signs and symptoms using a visual analog scale. Results: At T1, the median percent volume reduction was 13% for the IB group versus 19% for the AVCD group; at T7 it was 19% versus 26%, respectively ( p  < .001). The pressure of the IBs was significantly higher compared with the AVCDs at T0 (63 vs. 43 mmHg) but dropped by > 50% over time, while it remained unchanged with AVCDs owing to the periodic readjustment by the patient. Comfort was reported to be similar with the two compression devices. Conclusion: Re-adjustable AVCDs with a resting pressure of around 40 mmHg are more effective in reducing chronic venous edema than IBs with a resting pressure of around 60 mmHg. AVCDs are effective and well tolerated, not only during maintenance therapy, but also in the initial decongestive treatment phase of patients with venous leg edema.